Evaluating the gaps and intersections between marketing education and the marketing profession - Pinheiro, Margarida M. 1961-; Estima, Ana 1975-; Marques, Susana 1969- (IGI Global, 2019)
"This book focuses on the relationship between marketing education and marketing profession and the intersection between different stakeholders. It contains empirical, conceptual and theoretical contributions in marketing education. It also provides guidance on the redefinition of professional profiles and offers useful tools and insights for deeper and more productive intersections"--